Measuring postal access and direct delivery services among Native American reservations in Montana and South Dakota - Ryan Weichelt (Journal of Maps)
Over the past two decades voting by mail has increased. As the COVID-19 pandemic disrupted the 2020 political season, absentee voting increased to over 43% of all votes cast in the November Presidential Election. In recent years, many states have passed laws to limit the scope of absentee voting as necessary to curtail voter fraud. Though no evidence exists that fraud is more likely with mail-in voting, such laws have been found to have a disproportionate impact on some groups of voters more than others. This is true of many Native American communities that often rely on absentee voting. This study will utilize geospatial methods to examine postal realities for Native American on reservations in Montana and South Dakota. By illustrating where postal services are or are not located, a fuller contextual analysis of the issue can be provided. Such methods can enhance current methodologies utilized by political geographers.